Experimental Study on Deformation Behavior and Compressive Strength of Concrete Cast in Steel Tube Arches under Low-Temperature Conditions - Tuo Shi; Nianchun Deng; Xiao Guo; Wen Xu; Shi Wang (Advances in Materials Science and Engineering)
Taking the construction of a concrete-filled steel tube (CFST) arch bridge (part of the Sichuan-Tibet Railway) in low temperatures as the test site, firstly the deformation performance test of concrete was carried out. Following this initial testing, measurement of compressive strength and shrinkage performance was conducted in large-diameter CFSTs under a variety of curing conditions. Experimental results showed that the expansion effect of Ca-Mg composite expansive agent in concrete was better than that of other expansive agents at any stage. Under low-temperature curing (0°C), the sampling strength of the large-diameter CFSTs reached 73.5% of the design strength at 28 d in the presence of a nonthermal curing system. The design strength itself was reached, when a curing system involving a thermal insulation film was applied, and use of this film also led to improvements in concrete shrinkage. The results suggested that a Ca-Mg composite expansive agent, combined with an insulation film curing system, should be the technique selected for concrete pumping construction of CFST arch bridges in Tibet.